Effect of Overcrowding on Childhood Hospital Admissions for Acute Respiratory Infection: A Matched Case–Control Study - Fazal Badshah, Saad Farid, Mazhar Ali, Sumbal Afzal Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the association between in-house overcrowding and acute respiratory infections (ARIs) in children. Methods: This case-control hospital-based study wad conducted in Saidu Teaching hospital from March-2022 to December-2022. For cases we included 80 patients of age 6 to 59 months, who presented with newly diagnosed or relapsed cases of ARI. Controls were age and gender matched individuals who presented to outdoor hospital department for non-ARI evaluation and had no history of ARI since past 2 months. The in-house crowding was defined as >3 persons living in one bedroom in a home. Results: Mean age in this study was 18.3±8.9 months in ARI group and 19.7±7.8 months in control group (p-value 0.41). There were higher number of patients belonging to poor class in ARI group; 36 (45%) versus 21 (26.2%) in controls, 26 (32.5%) patients in ARI and 31 (38.7%) patients in controls were belonging to middle class, 18 (22.5%) patients in ARI and 28 (35.0%) patients in control group were belonging to upper class (p-value 0.03). Majority of patients in ARI group were from rural areas; 53 (66.3%) in ARI and 37 (46.3%) in control group (p-value 0.01). In-house overcrowding was found in 19 (20%) patients in ARI group and in only 9 (11.3%) patients in control group (p-value 0.03). Conclusion: In-house crowding is significantly associated with increased risk of ARI. The issue of overcrowding in rural regions is more serious than in cities. For Pakistani populations, the problem of overcrowded housing needs to be addressed. Keywords: In-house overcrowding, Acute respiratory infections, Rural living, socio-economic status.